Complex Thinking: A Systematic Review of Scientific Articles Indexed in Scopus 2016-2019 - Flores Morales, Jorge Alberto (2020)
Objective: To identify, systematically review and summarize the best available scientific evidence on the production of original and empirical articles on complex thinking. between the years 2016-2019. Method: The search was carried out using the Scopus database in open access, using references of the primary and secondary studies that were found. The search was carried out on the basis of the term "complex thought" or related, discarding those that do not refer to Edgar Morin's proposal. The result was 11 articles of work, of these those that did not fulfill the objective of the study have been excluded.